2019
DOI: 10.4103/genint.genint_1_19
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dose-Response Calibration Curve for Dicentric Chromosome Induced by X-Rays

Abstract: Chromosome aberration is a biomarker that has been used as a standard tool in biological dosimetry (biodosimetry) of individuals after exposure to ionizing radiation. It is based mainly on the induction of dicentric chromosomes – one of the radiation-induced biological effects, in order to correlate them with radiation dose. In this study, a dose calibration curve for X-rays was generated by using the dicentric assay and by fitting the data to both Chromosomal Aberration Calculation Software and Dose Estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Along with the high significance of the fitted C, α and β coefficients (z-test, P < 0.0001), the close to 1.0 p-value of the Poisson-based goodness of fit (χ 2 = 3.51, DF = 7, P = 0.83) indicates clearly excellent fitting of the data with no trend toward lack of fit (12). The comparison between our dose-response relationship for DC induction with those from similar published studies that used X-ray irradiation (19,26,(28)(29)(30)(31)(32)(33)(34)(35) showed quite large range of DC yields (Figure 6). These interlaboratory differences could emanate from the energy of the X-ray irradiation used, the dose rate, technical or methodical variances, metaphases and DC scoring criteria, and the professional experience of the scorers.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Along with the high significance of the fitted C, α and β coefficients (z-test, P < 0.0001), the close to 1.0 p-value of the Poisson-based goodness of fit (χ 2 = 3.51, DF = 7, P = 0.83) indicates clearly excellent fitting of the data with no trend toward lack of fit (12). The comparison between our dose-response relationship for DC induction with those from similar published studies that used X-ray irradiation (19,26,(28)(29)(30)(31)(32)(33)(34)(35) showed quite large range of DC yields (Figure 6). These interlaboratory differences could emanate from the energy of the X-ray irradiation used, the dose rate, technical or methodical variances, metaphases and DC scoring criteria, and the professional experience of the scorers.…”
Section: Discussionsupporting
confidence: 59%
“…These interlaboratory differences could emanate from the energy of the X-ray irradiation used, the dose rate, technical or methodical variances, metaphases and DC scoring criteria, and the professional experience of the scorers. For examples, although most authors used X-rays of 220-250 kVp (26,28,29,(32)(33)(34), others used 100-180 kVp (19,30,31,35). In addition, the dose rate varied from 1 Gy/min (26,30,32), to about 0.5 Gy/min (31,34), to 0.27 Gy/min or less (19,35) (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Biodosimetry Laboratory in Indonesia was established in 2005 by the National Nuclear Energy Agency of Indonesia, known locally as Badan Tenaga Nuklir Nasional (BATAN). Our research group within BATAN established the national standard dose-response calibration curves for DCA and MN in 2013, 2016, 2017, and 2019 [30][31][32][33][34]. The establishment of a national standard dose-response calibration curve for γH2AX is currently in progress in the laboratory.…”
Section: Current Status Of Automatization Of Biodosimetry Using Imagementioning
confidence: 99%
“…Effects of high/moderate ionizing radiation such as cell death, chromosomal aberrations, DNA damage, mutagenesis, and carcinogenesis are well understood and extensively studied (Barber et al 2002;Dubrova 2003;Joseph et al 2004;Saha 2012;Perumal et al 2015;Lusiyanti et al 2019), and the linear relationship between high doses of radiation and biological effects are well accepted. Research on how to improve radiotherapy has played an important role in the understanding of these relationships when a chronic exposure occurs.…”
Section: Introductionmentioning
confidence: 99%